A qualitative evaluation of community and acute hospital nursing oncology services in Ireland. (April 2021) - O'Mahony, Cian; Byrne, Stephen; Aherne, Joe; Hanan, Terry; Mullen, Louise; Keane, Maccon; Browne, Helen; Malee, Kathleen; Murphy, Kevin D.
Abstract: Purpose: Cancer patients are a particularly vulnerable population group, facing an increase in physical, mental, logistical and financial difficulties. This, as well as Ireland's increased focus on primary care with the Sláintecare health plan, led to the development of the Community Oncology Nursing Programme, where community nurses are trained to provide cancer care in the community. This paper sought to explore the lived experiences of the patients and nurses involved in this programme in order to examine its impact as well as determine facilitators and roadblocks for future development. Methods: A qualitative examination of the service was carried out by interviewing cancer patients receiving care as part of the programme as well as the nurses delivering care, both in the community and hospital day-ward. Thematic analysis was used. Results: Themes of improved patient experience, nurse-patient relationship, the importance of location and roadblocks to further implementation of the programme emerged. There was a universal belief that the programme offered benefits to the patient and improved their care in some manner. Conclusions: The Community Oncology Nursing Programme has been well received by both nurses and patients. The service provided by community nurses as part of this programme offers benefits to patients and an improved cancer service. Highlights: Previous studies have indicated a patient preference for cancer care delivered in the community. Cancer patients and nurses in both the community and day-ward were interviewed. There was universal acknowledgement of benefit from delivering care in the community. Patients particularly valued the relationship formed with their community nurse. Benefits to the patients' physical, mental and financial wellbeing were highlighted.